Application of genotyping by sequencing (GBS) for screening single nucleotide polymorphism (SNPs) associated with black tiger shrimp (Penaeus monodon) growth trait - Minh Thanh, Nguyễn Thị; Tâm, Nguyễn Quyết; Hảo, Nguyễn Văn; Sáng, Nguyễn Văn; Tôn, Nguyễn Đăng; Huyền Thương, Ma Thị; Phương Oanh, Kim Thị; Hải, Nông Văn; Hoa, Nguyễn Thị; Thu, Hà Thị; Hiền, Vũ Thị; Duy, Nguyễn Đình; et al. (Vietnam Journal of Biotechnology, 2018)
Nowadays, the black tiger shrimp (Penaeus monodon) farming in Vietnam still have to face a lot of problems, especially in the Country’s Shrimp Broodstock Production. To overcome these problems, we need a strategy for development of domesticated stocks of P. monodon and rational breeding programs for improved growth and disease resistance. Marker-assisted selection is a procedure that has been developed to avoid these problems associated with phenotypic selection, replacing the selection of the phenotype by selection using markers linked with quantitative trait loci (QTL). Application of next generation sequencing (NGS) associated with QTL to discover important molecular markers has been applied in many laboratories. In this study, we used genome typing by sequencing (GBS) with NGS for screening the SNPs related with growth trait to create a database for father study on the black tiger shrimp fast growth selection. Based on the putative genome sequences created by de novo assembly, 2887 SNPs have been screened, among them, 1799 SNPs appeared only in the fast growth population. Among the 287 annotated contigs, the two contigs were homologous with myosin heavy chain (MHC) associated with growth trait in crustacean species, contig83953 andcontig260347 were homologous with MHCa and MHC1, respectively. The two SNPs Contig83953:g.20T>C and Contig260347:g.19G>A were indicated. We hope that, these results will contribute to the black tiger shrimp genome database for further study to exploit the molecular markers for black tiger shrimp breeding and selections.